Development of a complex tertiary prevention intervention for the transition out of youth homelessness. (November 2018) - Vitopoulos, Nina A.; Frederick, Tyler J.; Leon, Scott; Daley, Mardi; McDonald, Carol; Morales, Shaniah; Cerswell Kielburger, Leysa; Cohen, Sue; Eacott, Karen; Howes, Carol; Gutierrez, Rose; McGavin, Karen; et al.
Abstract: This paper describes the process of design, development, and implementation of a complex, multi-component, tertiary prevention intervention aimed at stabilizing pathways out of homelessness, the Housing Outreach Project-Collaborative (HOP-C). HOP-C is a multi-organizational, cross-sector, inter-professional collaboration. This process-oriented paper aims to elucidate the rationale for and experience of implementing the three main components of HOP-C: case management, mental health treatment and peer support, as well as the processes that support this wrap-around intervention as a whole. This paper draws on qualitative process-oriented data (i.e. field notes and interviews with staff) collected over the course of the intervention, and integrates perspectives from multiple practitioners involved in this endeavour. Practitioners reported the diversity in the type and intensity of services offered to clients, the building of a close and communicative interprofessional and inter-agency team, as well as the development of broader connectivity between organizations and practitioners as significant strengths of this approach. Challenges and successes in implementation are explored with the intention of providing insight into ways in which other collaborative complex interventions might be approached in the youth homelessness sector. Highlights: Youth homelessness is a complex social problem HOP-C is a tertiary prevention complex intervention for youth transitioning from homelessness HOP-C represents a cross-sector, cross-agency, interprofessional collaboration Intervention provided wrap-around case management, peer, and mental health supports Individualized supports and close interprofessional teams linked to positive youth outcomes